Agonist and cholesterol modulate the alpha7 acetylcholine receptor in non-neural endothelial cells - Ayala Peña, Victoria Belen (2010)
The "neuronal" α7-type nicotinic acetylcholine receptor (α7AChR) is found in various non-neural tissues, including vascular 2+ endothelium, where its peculiar ionotropic (high Ca permeability) 2+ and metabotropic (Ca -mediated intracellular cascades) properties may play important roles in angiogenesis, inflammation and atherogenesis. Molecular properties of the α7AChR, its response to nicotine stimulation, and its cellular distribution were studied here using a combination of pharmacological, biochemical and fluorescence microscopy tools. α7AChRs in rat arterial endothelial cells (RAEC) were found to undergo agonist (nicotine)-induced upregulation (from 53±16 to 385.2±46.8 fmol/mg protein with 50 µM nicotine), increasing their cell-surface exposure. α7AChRs occurred predominantly in the “non-raft" subcellular fractions, yet cholesterol depletion mediated by cyclodextrin treatment reduced the number of cell-surface α7AChRs. Nicotine was found to increase the affinity of the α7AChR for crystal violet, an openchannel blocker. Under basal conditions, α7AChRs in endothelial cells displayed a high-affinity, presumably desensitized conformation (Kd ~0.76 nM), and both nicotine and cyclodextrin affected their cell-surface expression.